Propagating properties of traffic flow on a ring road without ramp - Tang, T.; He, J.; Wu, Yong Hong; Caccetta, Louis (Elsevier, 2014)
In this paper, we study the propagating properties of traffic flow on a ring road with no ramp. The numerical results show that the traffic flow on the ring road with no ramp can be divided into three traffic states and that the propagating property and proportion of each state, and the deviation between the current traffic state and its equilibrium state are related to the initial density. Finally, the video data of the third ring road in Beijing qualitatively testify the numerical results.